Outcomes of individualized nursing interventions: a systematic review of iterature - César Fonseca; Ana Ramos; José Vilelas; Cidália Castro; Maria Antónia Botelho (Rev Rene)
Health outcomes associated with individualized nursing care are essential to ensure their quality, of which its study is a priority. This study aims to identify the gains of individualized nursing interventions for middle-aged and elderly. It stands for a systematic review of the literature from 2004 - 2009, with the PICO method in EBSCO (CINAHL, MEDLINE). The research yielded 530 articles, of which 9 were selected. Nursing individualized interventions were identified such as health education, therapeutic touch, case management and tele-care. Concerning gain for people over 45 years of age were found effectiveness for self-care, decreased fatigue, increased information about health / illness, satisfaction with care, symptom management and medication regimen.